EU's Regulation of Geographical Indications and their Effects on Trade Flows - Daniel Leufkens (German Journal of Agricultural Economics (GJAE), 2017)
Nowadays one of the big issues in international trade is the so-called Transatlantic Trade and Investment Partnership (TTIP), a bilateral trade agreement between the EU and USA. In these negotiations there are still many open questions, including dealing with the European protection of geographical indications (GIs). The objective of this paper is, therefore, to evaluate the impact of different GI products and protection levels in bilateral trade partnerships between the EU itself and third countries for the purpose of food policy recommendations in current negotiation processes. Based on panel data on agri-food trade of EU member countries with all trading partners for the period from 1996 to 2010, a gravity approach is used to estimate bilateral trade effects of GIs. The findings suggest that the protection of diverting products and levels for GIs have opposite effects on EUs trade partnerships. As results, considering EUs overall trade, GIs on wines and spirits only have a trade-creating effect if these are highly protected, while for other agricultural products only lower protection levels increase bilateral trade significantly.
Keywords: 330